Evaluation of some 4-aryl-3-arylamino-5-imino-1,2,4-thiadiazolidines as potential anticonvulsant and analgesic compounds - Srivastava K.; Pandeya S.N. (My University, 2025)
A series of 4-aryl-3-arylamino-5-imino-1,2,4-thiadiazolidines (1a-k) and 4-aryl-3-arylamino-5-oxo-1,2,4-thiadiazolidines (2a-k) were evaluated for their anticonvulsant and analgesic activity. Substitution of p-methoxy group (1g) in the aryl ring resulted in more active compounds than the standard drug phenytoin in the MES test, whereas in the chemoshock test the compounds were found inactive. In the analgesic test most of the compounds exhibited analgesic activity with particular reference to p-Br (1k) and m-Cl (1i) substitutions which were most potent in this series.